History Education and the use of textbooks into the challenges of twenty fist century. Interview with Rafael Valls Montés - Gómez Carrasco, Cosme J.; Rodríguez Pérez, Raimundo A. (Historia y Memoria de la Educación, 2017)
The interview with Rafael Valls Montés addresses the importance of the textbook in teaching history. It is the most-used didactic resource in both Primary and Secondary Education in Spain. Dr. Valls is the specialist who has most studied the use of textbooks by teachers as well as their contents and activities. With an eye constantly on historiographical and psycho-pedagogical advances (Spain, Europe and America) and political context, the overall evolution can be considered positive. Since the 1970s, the creation of textbooks has been influenced by the idea of «total history», of the Annales School, with the inclusion of political, social, economic and cultural contents. However, school textbooks are still marked by numerous stereotypes, both factual and positivist, that detract from their usefulness. In addition, they tend to contribute to a lack of innovation in the teaching methodologies employed (reduced to lectures), resulting in students’ becoming passive receivers, obliged to memorize conceptual questions. The other great drawback of the school manual is that it essentially functions as a creator of identities: Spanish, European and, to a lesser extent, regional. This derives from a legacy of nineteenth-century nationalisms, which do not fit the multicultural reality of society as reflected in today’s classrooms. However, the manual is ultimately the result of the spirit of a succession of educational laws and, although its format may change it is bound to remain an essential resource for teaching and learning history. Moreover, it should serve as a stimulus for civic and innovative education